Jewish law and contemporary issues - Bleich, J. David; Jacobson, Arthur J. (Cambridge : Cambridge University Press, 2015)
Organized as a series of authoritative discussions, this book presents the application of Jewish law - or Halakhah - to contemporary social and political issues. Beginning with the principle of divine revelation, it describes the contents and canons of interpretation of Jewish law. Though divinely received, the law must still be interpreted and'completed' by human minds, often leading to the conundrum of divergent but equally authentic interpretations. Examining topics from divorce to war and from rabbinic confidentiality to cloning, this book carefully delineates the issues presented in each case, showing the various positions taken by rabbinic scholars, clarifying areas of divergence, and analyzing reasons for disagreement. Written by widely recognized scholars of both Jewish and secular law, this book will be an invaluable source for all who seek authoritative guidance in understanding traditional Jewish law and practice.
The nature and structure of Jewish law -- Divorce -- Jewish law and the state's authority to punish crime -- The Sotheby sale -- Torture and the ticking bomb -- War -- Dead or alive? -- Rabbinic confidentiality -- Cloning -- A note on Halakhic sources.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Jewish law